Signatures of omicron-like adaptation in early SARS-CoV-2 variants and chronic infection - Mark Tsz Kin Cheng; Mazharul Altaf; Jesu Castin; Ann-Kathrin Reuschl; Benjamin L. Sievers; Kimia Kamelian; Dejan Mesner; Rebecca B. Morse; Adam Abdullahi; Bo Meng; Kata Csiba; Steven A. Kemp; et al. (Cell Reports)
Summary: Persistent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections are a source of new variants and can provide insight into evolutionary trajectories. Here, we observe upper airway-specific evolution of SARS-CoV-2, demonstrating a fusion peptide (FP) domain mutation (S:P812S) adjacent to the S2′ cleavage site that emerged during a chronic infection. Indeed, this mutation had emerged previously and been transmitted in a delta variant lineage. P812S in a spike-pseudotyped virus did not impact entry efficiency. However, cleavage at S1/S2 was reduced, and molecular dynamics simulation demonstrated altered S1/S2 loop conformations. Consistent with impaired S1/S2 cleavage, and reminiscent of Omicron BA.1, cell-cell fusogenicity was severely impaired by P812S. P812S conferred evasion of a FP-targeting monoclonal antibody, consistent with FP-region structural rearrangements. Finally, P812S-bearing viruses showed evasion of polyclonal neutralizing antibodies in sera from vaccinated individuals at 32C. These data shed light on the balance between SARS-CoV-2 upper airway adaptation/immune evasion, syncytium formation, and pathogenic potential.